A long road ahead to reliable and complete medicinal plant genomes - Ling-Tong Cheng; Zi-Long Wang; Qian-Hao Zhu; Min Ye; Chu-Yu Ye (Nature Communications)
Abstract Long-read DNA sequencing has propelled medicinal plant genomics forward, with over 400 genomes from 203 plants sequenced by February 2025. However, many genomes still have assembly and annotation flaws, with only 11 gapless telomere-to-telomere assemblies. The core challenge remains identifying genes linked to secondary metabolite biosynthesis, regulation and evolution. High-quality complete genomes are essential for characterizing biosynthetic gene clusters and for enabling robust functional genomics and synthetic biology applications. We propose to focus on achieving more complete genome assemblies in diverse varieties on the basis of refining the currently available ones, leverage lessons from crop genomics research, and apply the cutting-edge genomics technologies in research of medicinal plant genomics.